IMPACT OF WORK READINESS ON CAREER SELF-EFFICACY AND CAREER EXPLORATION: A TWO-STEP MODEL - IFTIKHAR , BILAL MAKKI (2016)
Employers expect engineering graduates to be skilled and well equipped with selfbelief before getting into the workplace. However, most of the graduates lack these aspects. Due to deficiency of skills and self- belief in their capabilities, engineering graduates often find it hard to explore career opportunities. To address this issue, Washington accord established work readiness attributes for engineering graduates that includes fundamental knowledge and design, modern tool usage, project management and finance, engineers' society and environment, teamwork, ethics, communication and lifelong learning. This research in turn attempts to explore the literature on work readiness that significantly contribute to increased career self-efficacy which leads to effective career exploration. Eventually, a two-step framework is developed to examine; the impact of work readiness on career self-efficacy and, in turn, career self-efficacy's impact on career exploration.